South Asian Rivers A Framework for Cooperation (The Anthropocene: Politik-Economics-Society-Science,, 2018)
This volume identifies existing statist approaches and political economies of river management in South Asia. These rivers are heavily suffering from millions of people who in contrast consider them as holy and worship them. Edited by Professor Imtiaz Ahmed, the contributors of this book from India, Nepal and Pakistan are leading readers on a journey through the transboundary rivers of South Asia where rivers are vital for the life and living. The book explains why the region needs a framework for cooperation on the wellbeing of these rivers. River management is the key to sustaining healthy river systems. The authors stress that right of the rivers must be codified and guaranteed by the state and the people in South Asia. However, the statist approach to the transboundary rivers in South Asia actually conceives them as national rivers. This volume contributes to the current campaign of overcoming the water dystopias in South Asia.